การดำเนินงานและช่องทางการเผยแพร่รายการ ของสถานีวิทยุโทรทัศน์การศึกษาทางไกลผ่านดาวเทียม วังไกลกังวล - ทิพาพรรณ รัตนคอน (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
To study program management and distribution channels, including the operation of Distance Learning Television Station Wang Klai Kang Won. System theory, concept relating to production process of educational television, knowledge about diffusion of information via distance learning, including McQuail s Mass Media Organization and Social Power Model collectively provide conceptual framework for the study. The researcher obtains data from in-depth interview with management team and staff of Distance Learning Television Station Wang Klai Kang Won in addition to documents distributed by the station, such as brochure and leaflets. The findings of the research are as follows. The operation of Distance Learning Television Station Wang Klai Kang Won is based solely on public interest. The station obtains support and assistance in terms of input, e.g. personnel, budget, management and logistics, from individuals and organizations, both public and private sectors. The goal of the station is to provide people with an equal opportunity in education which should prove useful for future development of the entire nation. Educational programs, both general knowledge and vocational, are aired 24 hours daily, using 14 signal sources. Altogether, there are 4 distribution channels, namely, DTH , UBC, community cable and Internet. The station s overall performance helps solve the problems relating to an inadequacy of teachers. It also improves the quality of educational system to a significant degree, especially in remote areas. Once the people get better education, they are likely to do well in their career. Hence, their standard of living should improve eventually.